Noninvasive Transcutaneous Vagus Nerve Stimulation Decreases Whole Blood Culture‐Derived Cytokines and Chemokines: A Randomized, Blinded, Healthy Control Pilot Trial. Issue 3 (15th March 2016) - Lerman, Imanuel; Hauger, Richard; Sorkin, Linda; Proudfoot, James; Davis, Bryan; Huang, Andy; Lam, Katie; Simon, Bruce; Baker, Dewleen G.
Abstract : Objectives: The purpose of this study was to test the transcutaneous noninvasive vagus nerve stimulator (nVNS) (gammaCore©) device to determine if it modulates the peripheral immune system, as has been previously published for implanted vagus nerve stimulators. Materials and Methods: A total of 20 healthy males and females were randomized to receive either nVNS or sham stimulation (SST). All subjects underwent an initial blood draw at 8:00am, followed by stimulation with nVNS or SST at 8:30am . Stimulation was repeated at 12:00pm and 6:00pm . Additional blood samples were withdrawn 90 min and 24 hour after the first stimulation session. After samples were cultured using the Myriad RBM TruCulture (Austin, TX) system (WBCx), levels of cytokines and chemokines were measured by the Luminex assay and statistical analyses within and between groups were performed using the Wilcoxon Signed Ranks Test and Mann‐Whitney U with the statistical program R. Results: A significant percent decrease in the levels of the cytokine interleukin [IL]‐1β, tumor necrosis factor [TNF] levels, and chemokine, interleukin [IL]‐8 IL‐8, macrophage inflammatory protein [MIP]‐1α, and monocyte chemoattractant protein [MCP]‐1 levels was observed in the nVNS group non‐lipopolysaccharide (LPS)‐stimulated whole blood culture (n‐WBCx) at the 24‐hour time point ( p  < 0.05). In SST group, there was a significant percent increase in IL‐8 at 90 min post‐stimulation ( p  < 0.05). At 90 min, the nVNS group had a greater percent decrease in IL‐8 concentration ( p  < 0.05) compared to SST group. The nVNS group had a greater percent decrease in cytokines (TNF, IL‐1β) and chemokines (MCP‐1 and IL‐8) at 24 hour ( p  < 0.05) in comparison to SST. LPS‐stimulated whole blood cultures (L‐WBCx) did not show a significant decrease in cytokine levels in either the nVNS or SST group across any time points. The nVNS group showed a significant percent increase in LPS‐stimulated IL‐10 levels at the 24‐hour time point in comparison to SST. Conclusions: nVNS downregulates inflammatory cytokine release suggesting that nVNS may be an effective anti‐inflammatory treatment.